Rapid thermodynamically stable complex formation of [nat/111In]In3+, [nat/90Y]Y3+, and [nat/177 Lu]Lu 3+ with H 6 dappa - Kostelnik, Thomas I.; Wang, Xiaozhu; Southcott, Lily; Wagner, Hannah; Kubeil, Manja; Stephan, Holger; Jaraquemada-Peláez, María de Guadalupe; Orvig, Chris (Inorganic chemistry, 2020)
A phosphinate-bearing picolinic acid-based chelating ligand (H6dappa) was synthesized and characterized to assess its potential as a bifunctional chelator (BFC) for inorganic radiopharmaceuticals. Nuclear magnetic resonance (NMR) spectroscopy was employed to investigate the chelator coordination chemistry with a variety of nonradioactive trivalent metal ions (In3+, Lu3+, Y3+, Sc3+, La3+, Bi3+). Density functional theory (DFT) calculations explored the coordination environments of aforementioned metal complexes. The thermodynamic stability of H6dappa with four metal ions (In3+, Lu3+, Y3+, Sc3+) was deeply investigated via potentiometric and spectrophotometric (UV-vis) titrations, employing a combination of acidic in-batch, joint potentiometric/spectrophotometric, and ligand-ligand competition titrations; high stability constants and pM values were calculated for all four metal complexes. Radiolabeling conditions for three clinically relevant radiometal ions were optimized ([111In]In3+, [177Lu]Lu3+, [90Y]Y3+), and the serum stability of [111In][In(dappa)]3- was studied. Through concentration-, time-, temperature-, and pH-dependent labeling experiments, it was determined that H6dappa radiolabels most effectively at near-physiological pH for all radiometal ions. Furthermore, very rapid radiolabeling at ambient temperature was observed, as maximal radiolabeling was achieved in less than 1 min. Molar activities of 29.8 GBq/μmol and 28.2 GBq/μmol were achieved for [111In]In3+ and [177Lu]Lu3+, respectively. For H6dappa, high thermodynamic stability did not correlate with kinetic inertness—lability was observed in serum stability studies, suggesting that its metal complexes might not be suitable as a BFC in radiopharmaceuticals.